Objective vs. Subjective Health in Very Advanced Ages: Looking for Discordance in Centenarians - Araújo, Lia; Teixeira, Laetitia; Ribeiro, Oscar; Paúl, Constança (Frontiers in Medicine, 2018)
Background: Living beyond one hundred years of age is associated with several functional and health constraints but their impact depends on one’s perception of the situation. Associations between self-rated health (SRH) with sociodemographic and psychosocial variables have been explored in several studies, revealing that one’s health appraisal depends of factors beyond the objective health condition. There is a large body of literature concerning SRH in later life but lack of evidence about centenarians’ perception of health and its associated factors, which could increase the available knowledge on the strengths and resources individuals in very advanced ages have for facing daily life limitations. Objective and Methods: This study aims to analyse the relationship between subjective and objective health status in a sample of centenarians (n=127). Subjective health was assessed by a single-item health measure, and objective health by considering the number of reported diseases and a functional capacity scale (BADL and IADL). Main health characteristics are described as well as examined the association between objective and subjective health. Results: 46.5% of the sample has a good, very good or excellent appraisal of their own health. SRH was associated (p < 0.05) with BADL and IADL scores and with the total number of diagnosis; when analysing SRH according to the level of functional capacity, results revealed that most individuals with severe and moderate dependence have a reasonable to excellent SRH (p > 0.05). Conclusion: Having diseases and functional dependence at one hundred years old may not mean to have a bad SRH. The high variability in SRH and the discordance between objective and subjective measures are a proof of centenarian´s capacity of adaptation and the existence of individual resources, which may be decisive for one’ perception and handling of health situation at such an advanced age.